A study on the relationship between mathematic problem solving skills and career choices among selected secondary school students in Alor Setar, Kedah - Nor Syamimi Mohamed Adnan (Institute of Education, International Islamic University Malaysia, 2014)
This study highlight the importance of helping students discover and better comprehend their level of mathematic problem solving skill and its relationship to their mathematics career choice.